The Preparation of University Teachers Internationally - ICED (International Consortium for Educational Development, 2014)
To mark twenty years since its foundation ICED surveyed member networks in 2013 to identify current policies and practices related to the preparation of teachers in higher education internationally. There is little systematic gathering of national data on the preparation of university teachers. The responses provided a rich source of qualitative data which were summarised in a draft report discussed and revised at the 2013 ICED Council meeting in Kyoto. This report presents key findings from the survey, supplemented by information from Network annual reports to ICED Council.